PERSENTASE BUAH JADI PADA PERSILANGAN KELAPA GENJAH SALAK DENGAN KELAPA DALAM MAPANGET (GSK x DMT) - Runtunuwu, Semuel D.; Pongoh, Jantje; Tampake, Heldering; Pamandungan, Yefta (EUGENIA, 2007)
ABSTRACT Runtunuwu, S.D., et.al. 2007. The Become Fruit Rate in Crossing Coconut Genjah Salak x Dalam Mapanget (GSK x DMT). Eugenia 13(1):97-108. The aim of this research was 1) individu tree crossing of coconut Genjah Salak x Dalam Mapanget (GSK x DMT), 2) to known the become fruit rate in crossing individu tree of coconut GSK x DMT. The method of crossing used crossing a pair between fourteen trees individu of coconut GSK. With three trees coconut DMT, so it become fourty two combination crossing. Coconut DMT 1188 crossing with stem number one of coconut GSK, DMT 1172 with stem number two coconut GSK and DMT 781 with stem number three. The become fruit rate of the crossing result between fourteen individu trees of coconut GSK and tree individu trees of DMT with the tree number 1188, 1172 and 781 in three mounth in sequence was have variation from 0,00 – 27,27 %, 3,76 – 32 % and 2,86 – 27,16 %. Therefore the lowest success rate of these crossing was in combination of GSK coconut tree number fourteen and DMT tree number 1188 was 0,00 %, while the highest success rate was in the combination crossing between coconut GSK tree number 12 and DMT tree number 1172 was 32 %. Keywords: coconut, fruit rate, crossing